2019
DOI: 10.1111/cch.12653
|View full text |Cite
|
Sign up to set email alerts
|

Information as a crucial factor for toilet training by parents

Abstract: Background: Toilet training (TT) is a milestone in a child's development. Nowadays children complete TT later than previous generations. This can have detrimental consequences for the child, the parents and the environment. TT is experienced as difficult and time consuming, parents could benefit from guidelines to assist in this process.Methods: Focus group discussions (FGDs) were used to explore parents' experiences in an inductive approach applying purposive sampling. The FGDs aimed to explore the type of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…While there are very few studies on the types of social support parents desire with toilet training, this study adds to emerging evidence that instrumental support may prove critical. In the one qualitative study by Van Aggelpoel et al ( 2019 ), Belgian parents were asked about the kinds of informational support they seek with toilet training. But parents also described the importance of receiving tangible, instrumental help from others, including grandparents and teachers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While there are very few studies on the types of social support parents desire with toilet training, this study adds to emerging evidence that instrumental support may prove critical. In the one qualitative study by Van Aggelpoel et al ( 2019 ), Belgian parents were asked about the kinds of informational support they seek with toilet training. But parents also described the importance of receiving tangible, instrumental help from others, including grandparents and teachers.…”
Section: Discussionmentioning
confidence: 99%
“…But parents also described the importance of receiving tangible, instrumental help from others, including grandparents and teachers. As one parent explained, “Everyone has to join in” (Van Aggelpoel et al, 2019 ). This growing evidence‐base for the stress‐support matching hypothesis highlights the importance of understanding which types of social support caregivers desire for a given childcare practice in order to design effective programming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toilet training is affected by physiological, psychological, and sociocultural factors. 2,3 Culture is an important factor affecting the time and method of toilet training. 4 In many cultures, parents regard the achievement of independent toileting as a significant accomplishment and a step toward self-sufficiency.…”
Section: Introductionmentioning
confidence: 99%
“…4 On the other hand, it has been reported that toilet training, which is started late, causes such problems as constipation and urinary retention. 3 In addition, cognitive development, especially speaking ability, is important to start education because; the child must say that the toilet is coming. 5 Toilet training is an important stage and a milestone in the development of the child.…”
Section: Introductionmentioning
confidence: 99%